2006
DOI: 10.1007/s10339-006-0035-0
|View full text |Cite
|
Sign up to set email alerts
|

Timing in cognition and EEG brain dynamics: discreteness versus continuity

Abstract: This article provides an overview of recent developments in solving the timing problem (discreteness vs. continuity) in cognitive neuroscience. Both theoretical and empirical studies have been considered, with an emphasis on the framework of operational architectonics (OA) of brain functioning (Fingelkurts and Fingelkurts in Brain Mind 2:291-29, 2001; Neurosci Biobehav Rev 28:827-836, 2005). This framework explores the temporal structure of information flow and interarea interactions within the network of func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
106
0
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(110 citation statements)
references
References 207 publications
(231 reference statements)
2
106
0
2
Order By: Relevance
“…Scale-free neocortical dynamics was also ascertained by Freeman (2005) in the electroencephalogram of rabbits; a computer model also suggested that neodortex is stabilized in a scale free state of self-organized criticality. Quantitative fMRI analysis of functional connectivity (Eguiluz et al, 2005, Chialvo, 2004 and EEG analysis of functional connectivity (Fingelkurts and Fingelkurts, 2006) supply additional evidence. reviewed recently the numerous literature sources which identify brain neural networks as 'scale free'.…”
Section: : Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Scale-free neocortical dynamics was also ascertained by Freeman (2005) in the electroencephalogram of rabbits; a computer model also suggested that neodortex is stabilized in a scale free state of self-organized criticality. Quantitative fMRI analysis of functional connectivity (Eguiluz et al, 2005, Chialvo, 2004 and EEG analysis of functional connectivity (Fingelkurts and Fingelkurts, 2006) supply additional evidence. reviewed recently the numerous literature sources which identify brain neural networks as 'scale free'.…”
Section: : Discussionmentioning
confidence: 99%
“…It can now be given an operational meaning: rather than viewing integration-separation as polar opposites, a continuous scale of tendencies for neural groups to coordinate and segregate seems more appropriate. At the level of neuronal dynamics, this continuum appears to be supported by the flexibility of coupling coefficients among diverse neuron groups (Friston, 1997(Friston, , 2000: that is, in the form of a continuum of dynamically shifting, discrete configurations of neuron networks (for review: see Fingelkurts and Fingelkurts, 2006). The expression of this is the meandering of the system's representation in phase space, dictated by its intrinsic dynamics and external influences.…”
Section: 1: On Coordination Dynamics and Metastabilitymentioning
confidence: 99%
“…Different methods of data analysis revealed characteristic discontinuities in the EEG record which, in the view of Fingelkurts and Fingelkurts (2006), are alternative levels of description, complementary to continuous data records. In a series of studies, these authors identified rapid transitions occurring in the amplitude of continuous EEG activity which mark the boundaries between quasi-stationary segments of activity (Fingelkurts and Fingelkurts, 2001, 2005Kaplan et al, 1997).…”
Section: The Macroscopic Scalementioning
confidence: 99%
“…Scale-free neocortical dynamics was also ascertained by Freeman (2005) in the electroencephalogram of rabbits; a computer model also suggested that neodortex is stabilized in a scale free state of self-organized criticality. Quantitative fMRI analysis of functional connectivity (Eguiluz et al, 2005, Chialvo, 2004 and EEG analysis of functional connectivity (Fingelkurts & Fingelkurts, 2006) supply additional evidence. Sporns et al (2004) reviewed recently the numerous literature sources which identify brain neural networks as 'scale free'.…”
Section: Dynamics In Dynamic Core and The Global Neuronal Workpacementioning
confidence: 99%
“…Participants' reports can thus be useful in identifying variability in brain activity from moment to moment; this unique information might guide the detection and interpretation of neural processes correlated to different aspects of conscious experience. Novel techniques for EEG analysis might be fruitfully applied in that framework (Fingelkurts and Fingelkurts 2006;Thompson and Varela 2001).…”
Section: Neuroscience Of Meditation and Consciousnessmentioning
confidence: 99%